Structural Behaviour Of Distressed And Strengthened Post-Tensioned Box Girder Beams - Bukola Ohu, Rachael (2007)

(untitled)
Box girder prestressed concrete beams are used widely in bridge construction due to its efficient structural response under flexural as well as torsional loading. Prestressing can be either internally or externally applied to a beam. Every year, many prestressed concrete bridge girders are damaged due to accidental load and /or due to an aggressive environment surrounding the bridge. Corrosion and /or snapping of prestressing cables will cause serious damage in the bridge structure. Many researchers have covered the strengthening of prestressed concrete girders under flexure or under shear. Very limited research is available on the significance of different strengthening techniques under combined shear–flexural loading. Furthermore, torsional load is another important aspect which needs to be considered when discussing the strengthening techniques effect This research covers the effect of snapping of externally prestressed cables on the structural behaviour of box girder bridge beams subjected to a combined flexural – shear – torsional load. Five full scale box-girder beams were cast and tested experimentally. The first beam specimen acted as a control beam while in the remaining four beam specimens, 15% of the prestressing cable area was snapped. After snapping, one specimen was tested till failure and the other three specimens are strengthened using different techniques and tested till failure. To restore the beam capacity, three different strengthening techniques were used under the same load combination. The techniques adopted for this research are externally bonded CFRP laminates, extra longitudinal prestress cables and vertical prestressing applied by using bolts and nuts system. The results show that snapping of 15% of the prestressing cable will result in a 74% increase in deformation at service load and a 22% decrease in ultimate load. Furthermore, the snapping of the prestress wire will increase the stresses in the cables by 70% as compared to the unsnapped beam. All the strengthening techniques used can effectively restore the beam capacity at service and overcome the effect of cable snapping, however, at ultimate the restorative capacity of one of the strengthening techniques could not be fully established due to a localized failure.